Leading your Research Team in Science - Jansen, Ritsert C. (Life Sciences, 2018)
This short and practical guide offers valuable recommendations, stories and exercises, to guide readers towards a really successful career as an independent investigator in science. A must-read for early-career researchers, as well as those advising them and anyone else serious about science. This title is available as Open Access via Cambridge Core.